Organisational change theory and the use of indicators in general practice. Issue 3 (2nd June 2004) - Rhydderch, M; Elwyn, G; Marshall, M; Grol, R
Abstract : General practices are making greater use of indicators to help shape and develop organisational arrangements supporting the delivery of health care. Debate continues concerning what exactly such indicators should measure and how they should be used to achieve improvement. Organisational theories can provide an analytical backdrop to inform the design of indicators, critique their construction, and evaluate their use. Systems theory, organisational development, social worlds theory, and complexity theory each has a practical contribution to make to our understanding of how indicators work in prompting quality improvements and why they sometimes don't. This paper argues that systems theory exerts the most influence over the use of indicators. It concludes that a strategic framework for quality improvement should take account of all four theories, recognising the multiple realities that any one approach will fail to reflect.